Interlinking-Based Teaching: A Study on the Development of the Interlinking Index Framework - Bozkurt, Salih; Ozdemir, Oguz (Science Insights Education Frontiers, 2026)
In interlinking-based teaching, designing and implementing instructional content and practices based on interlinking has become a necessity for solving real-life problems and understanding various phenomena encountered in daily life. However, the lack of comprehensive models that guide interlinking-based instructional processes constitutes a significant gap in the literature. In this context, the present study aims to develop an analysis tool that can guide the development, implementation, and evaluation of interlinking-based instructional content. To this end, a comprehensive literature review was conducted, and the collected data were analyzed through content analysis by two researchers. The inter-coder reliability was calculated as 89%. Subsequently, an “interlinking index” was developed and submitted for expert review. Based on the feedback received from the experts, the index was revised and finalized. The resulting “analysis index” consists of 17 items grouped under four main dimensions, providing guidance for the development, implementation, and evaluation of interlinking-based instructional content. It is expected that this study will contribute to the dissemination and effective use of interlinking-based instructional activities.